2016
DOI: 10.3923/rjmp.2016.89.97
|View full text |Cite
|
Sign up to set email alerts
|

Green Coffee Extract Protects H9C2 Cardiomyocytes from Doxorubicin Induced Apoptosis

Abstract: Green Coffee Extract (GCE), an extract of Coffea arabica bean is a popular health supplement employed for anti-obesity and anti-diabetic effects. Here a hydroalcoholic extract of Green Coffee (GCE) was evaluated for its potential as a cardioprotective agent against Doxorubicin (Dox) induced cardiac insult in a H9C2 rat cardiomyocyte in vitro model system. The GCE was tested in an MTT viability assay using 1 μM Dox with and without GCE pretreatment at 50, 100 and 250 μg mLG 1 concentrations. GCE was also tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Preventing Casp7 activation is a strong indicator of anti-apoptotic capacity. Malkapuram et al 54 demonstrated that prevention of Casp7 activation protects H9C2 cells from DOX-induced apoptosis. Our findings showed that periostin application downregulated myocardial expression of apoptotic executioner gene Casp7 from caspase family in the ISO-induced myocardial injury model in rats, which may reflect antiapoptotic function of periostin.…”
Section: Discussionmentioning
confidence: 99%
“…Preventing Casp7 activation is a strong indicator of anti-apoptotic capacity. Malkapuram et al 54 demonstrated that prevention of Casp7 activation protects H9C2 cells from DOX-induced apoptosis. Our findings showed that periostin application downregulated myocardial expression of apoptotic executioner gene Casp7 from caspase family in the ISO-induced myocardial injury model in rats, which may reflect antiapoptotic function of periostin.…”
Section: Discussionmentioning
confidence: 99%